2010
DOI: 10.1186/1755-7682-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 8 (IL-8) - a universal biomarker?

Abstract: Many clinical conditions including various types of cancers are complex and generally require invasive, laborious, expensive and time-consuming investigations for their diagnosis, treatment and follow-up. There is therefore a general need for exploring non-invasive markers in clinical medicine. Interleukin 8 (IL-8) is currently being applied in various subspecialties of medicine either for the purpose of rapid diagnosis or as a predictor of prognosis. Nevertheless, there is need for large-scale studies to subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 18 publications
1
70
0
3
Order By: Relevance
“…37 IL-8 mRNA is stable in many cell lines and cancer cells as reported here and by others. If in some cell types a sustained stable IL-8 mRNA is considered an aberration; the PMA/THP-1 differentiation system could be used as a simple and easy tool for in the depth molecular investigation of this novel form of sustained stabilization of a chemokine mRNA.…”
Section: Discussionsupporting
confidence: 49%
“…37 IL-8 mRNA is stable in many cell lines and cancer cells as reported here and by others. If in some cell types a sustained stable IL-8 mRNA is considered an aberration; the PMA/THP-1 differentiation system could be used as a simple and easy tool for in the depth molecular investigation of this novel form of sustained stabilization of a chemokine mRNA.…”
Section: Discussionsupporting
confidence: 49%
“…Cytokines are important mediators of inflammation and are usually associated with pathogenesis of many inflammatory diseases. Therefore, IL-8 is currently being applied as noninvasive diagnostic marker in various fields of medicine either for the purpose of early diagnosis or as a prognosis predictor [22]. Furthermore, recently, Ray et al [23] has identified 18 signaling proteins in blood plasma that can be used to classify and predict clinical Alzheimer's diagnosis, among which IL-8 has been also identified.…”
Section: ) Nacl Solution Measurementsmentioning
confidence: 99%
“…Secreted proteins play an important role in determination, control, and coordination of biological processes such as cell growth, differentiation, immune defense, and pathological processes such as cancer progression [1,2]. Comparing the secretome of cells in a normal as well as in a stressed situation, for example induced by inflammation or other disease states, may thus allow determining alterations which are characteristic for any given state [3].…”
Section: Introductionmentioning
confidence: 99%